Comportamento de misturas asfálticas tipo camada porosa de atrito (CPA) - Dresch, Fernanda (2016)
Road transport is extremely important for the development of Brazil and the increasing vehicular traffic in the transport of people gives an excessive dependence on roads. The quality of the road network of the country requires improvements to both structural aspects (resilience to the efforts required by traffic) as the functional in driving the vehicle, especially in terms of safety and acoustics, requiring the construction of increasingly discerning pavement and improved. Among the various types of asphalt blends, the asphalt blends of open type graded friction course (OGFC), presents some characteristics that serve as an alternative to the functional improvement of a pavement. In the present study verified the mechanical and functional behavior of five types of blends of OGFC to be used in construction of federal highways in Rio Grande do Sul, comparing with data from two Asphalt Concrete blends (AC) - (Range B and C). To determine the mechanical properties were used the tests resilient modulus (RM), tensile strength (RT) and testing Cântabro abrasion (PM), to investigate the functional properties were used sound absorption testing and hydraulic conductivity and finally to evaluate the structural contribution of the OGFC in flexible pavements a mechanistic analysis was carried out. The five OGFC mixtures were designated OGFC1, OGFC2, OGFC3, OGFC4 (with lime) and OGFC5 (with lime) and the mixtures of AC designated in ACB (Range B) and ACC (Range C). Samples OGFC and AC was determined the density parameters along with the volumetric properties, voids, empty bitumen ratio and other properties, being prepared with asphalt cements oil (CAP) 60/85 and CAP 55/75 respectively. In the test PM Cantabro it was observed that increasing the binder content leads to a consequent improvement in wear resistance. In RT assays, it was found that no peak maximum variable resistance trends in different amounts of binders, blends OGFC. In the RT assays, it was found that there are variable maximum strength values, in the different binder contents, in the OGFC mixtures. The RM test showed that the deformability of the blends increases as the amount of binder increases, and consequently decreases the value of RM, it being understood that the asphalt binder decreases the rigidity of the blends. The increase of temperature and decrease of charging frequency increases the deformability for all mixes for making a termosusceptivel behavior. In the sound absorption assay, the five OGFC blends exhibited fairly high absorption values with variations in peak absorption values between 0.90 and 0.98 between the 500 and 800 Hz frequency band. OGFC presented values of sound absorption higher than the values of dense asphalt mixtures found in the literature. The hydraulic conductivity test showed that the asphalt content directly influences the value of the hydraulic conductivity coefficient. With regard to the determination of the design content of the CPA blends, the only content that met all the specifications of the DNER-ES-386/99 standard was the 4% binder content. The OGFC1 mixture presented the best mechanical performance and the OGFC5 blend presented the best results from a functional point of view, but did not achieve good results from the mechanical point of view, presenting limit values required by standard DNER-ES-386/99. In relation to the values of deflection, horizontal deformation of traction and vertical deformation of compression, the OGFC caused a small contribution to the structure of the pavement generating a small decrease of these parameters. For the N of fatigue, a small contribution of the OGFC in the results of N of fatigue in the pavement was realized which took into consideration its use.